Microwave-Assisted Synthesis of 1,3,4-Oxadiazoles Containing Pyrazolones - Ravindranath, L.K.; Srikanth, K.; Ishrath Begum, D. (Asian Journal of Chemistry, 2010)
The key intermediate (Z)-2-(5-oxo-4-(2-phenyl hydrazono )-3-(trichloromethyl)-4,5-dihydro- 1H-pyrazole-1-yl)acetohydrazide (5) cyclization with aryl substituted acids 6a-h in presence of phosphorous oxy chloride (POCl3) under microwave irradiation resulted in the formation of the corresponding (Z)-1-((5-phenyl-2,3-dihydro-1,3,4-oxadiazole-2-yl)methyl)-4-(2-substituted aryl hydrazono)-3-(trichloromethyl)-1H-pyrazole-5(4H)one (7a-h) in quantitative yields. The results obtained indicate that, unlike classical heating, microwave irradiation results in higher yields, shorter reaction times (5-12 min) and cleaner reactions.